Evaluation of Sexual Dysfunction in Patients with Rheumatoid Arthritis. - Noroozi, Mohsen; Baeis, Mehdi Gholamzadeh; Borzooei, Shahin (Qom University of Medical Sciences Journal, 2016)
Background and Objectives: Rheumatoid arthritis is one of the most common autoimmune diseases, which affects about 1% of the world population. Rheumatoid arthritis may affect all aspects of life, including sexual function. In this study, sexual dysfunction was evaluated in patients with rheumatoid arthritis. Methods: This descriptive-analytical study was conducted in the first 6 months of 2015 in Qom city. The samples (N=120) were selected by available non-random method. Data collection tool was demographic characteristics questionnaire, Female Sexual Function Index (FSFI), International Index of Erectile Function (IIEF), and checklist of patient information, clinical examination, and laboratory data. The data were analyzed using Chi-square and t tests. The level of significance was considered less than 0.05. Results: The mean age of the samples was 39.2±9.3 years and the majority of the subjects were female (79.2 %). Sixty-four subjects (53.3%) had sexual dysfunction. The prevalence of sexual dysfunction in female patients was higher, which was statistically significantly different (p=0.016). Conclusion: The results of this study showed that there is a relationship between rheumatoid arthritis and sexual dysfunction, therefore, it is recommended that health care staff accurately and more importantly follow this issue in patients with rheumatoid arthritis and that serious screening be performed for all patients with rheumatoid arthritis, especially women.